Hombres de estado / [J. Calmette ; traducción del francés por Arturo Orzabal Quintana] - Calmette, JosephOrzábal Quintana, Arturo (Nueva Colección Clío)
Contiene: Luis XI/J. Calmette. -- Lorenzo el Magnífico/Agustín Renaudet. -- Felipe II de España/Rafael Altamira. -- Catalina II/P. Milioukov. -- Metternich/André Robert. -- Cavour/Georges Bourgin. -- Disreali/Andrés y Daniel Toledano